MOVAA -a mobile fashion trucks - Abdul Rahman, Julaila; Noor Azahar, Hawa Syakirah; Jasmani, Ismail (2020)
Street market plays a significant role in the Malaysian’s economy. The street markets reflect a piece of the unique Malaysian culture for they portray the buying and eating preferences, interaction patterns and leisure activities among various ethnic groups. Nevertheless, street market vendors face many challenges such as safety and cleanliness of their stalls, the confusing legal and regulatory aspects, and many more. Today, as the truck vendors are getting popular in Malaysia, it is an opportunity for street vendors to explore various advantages offered by businesses using trucks. This research aims to develop Mobile Fashion Trucks. There are three (3) objectives of this study, to identify existing elements that needed for the mobile vendor in apparel retail, to study the existing spatial layout for vendors’ truck ,and to identify the user preference on features for a display area in the vendors’ truck. Three methods are adopted to achieve the above-set objectives; 1) line-up study on existing mobile fashion trucks; 2)checklist on the spatial layout of the truck, and 3) questionnaire survey. The findings are that three (3) elements are required to upgrade for a mobile fashion truck: (i) exterior (fast set-up),(ii)interior (spatial layout) and (iii) display features. The design model was developed based on the findings of the three (3) elements. Design ideas visualizing the best image for the mobile fashion trucks were continually developing.